Exploring the psychometric properties of the French revised test anxiety + regulatory scale in Swiss secondary school students - Valls, Marjorie (Frontiers in Education, 2023)
Although test anxiety had traditionally been conceptualized as composed of negative dimensions, the French Revised Test Anxiety + Regulatory scale (FRTA+R) includes a noteworthy positive dimension which represents the regulatory component of anxiety. Perceived Control is thus supposed to reflect a potential coping capacity. This study investigates the psychometric properties of the FRTA+R using confirmatory factor analysis, as well as its reliability and invariance across gender and grade levels in a sample of 259 secondary school students from a French-speaking canton of Switzerland (Mage = 13.51, SD = 1.05; 51% girls). The aim is also to identify test anxiety profiles using cluster analysis. The main findings support the five-factor structure of FRTA+R (CFI = .97; TLI = .97; RMSEA = .047) and confirm invariance across gender and grade levels at both configural, metric and scalar levels. While the reliability of the scale is broadly supported, the Test-irrelevant thinking factor presents relatively heterogeneous factor loadings, suggesting a possible lack of precision and stability. Findings from latent mean comparisons showed that girls reported higher levels on three dimensions (i.e., Bodily symptoms, Tension and Worry) as well as lower levels of Perceived control than boys, while 9th graders also reported higher levels on these three negative dimensions compared to 10th and 11th graders. A preferred 3-cluster solution was identified, corresponding to low (41% of whom 66% boys), medium (37% of whom 60% girls) and high (22% of whom 72% girls) levels of test anxiety. Although the pertinence of defining test-irrelevant thinking and perceived control as a full-fledged dimension of test anxiety is questioned, results contribute to the extensive body of research supporting gender differences and are also discussed in terms of practical implications and benefits of FRTA+R.